Structure sensitivity of parameters of acoustic relaxation а-peak in niobium and iron - Natsik, V.D.; Pal-Val, P.P.; Pal-Val, L.N.; Semerenko, Yu.A. (Functional Materials, 2004)
Influence of dislocation structure on parameters of low-temperature internal friction а-peak and related Young’s modulus defect has been studied in niobium single crystals and polycrystals and pure iron single crystals. A statistical interpretation of the temperature dependence and structure sensitivity of dynamic relaxation characteristics in the vicinity of а-peak has been proposed based on assumed random scatter of activation energy of elementary relaxators. The attempt period, average value, and dispersion of activation energy have been estimated for the relaxation process responsible for the а-peak in the materials studied.